Recent trends of snow avalanche regime in the Central Caucasus (Elbrus region as an example) - A. D. Oleinikov; N. A. Volodicheva (Лëд и снег)
The climate change during cold seasons of 1995–2017 in the Central Caucasus is estimated, and its influence on the avalanche regime is shown. Data on the avalanche releases in the Central Caucasus for the period 1968– 2017 together with observations of high-altitude meteorological stations were used for the analysis. The paper presents estimates of snowiness of the winters and their frequency of occurrence in the area under investigation. The winter snowiness was noted to decrease since the beginning of the 2000s. The last decade of the period was not snowy, especially its series of six winters having very small amounts of snow. It is shown that in the second half of the XX century the heaviest snowfalls took place mostly in Januaries, and they were followed by releases of avalanches with the volumes exceeding 1 million cubic metres. In the early 2000‑ies, intensive January snowfalls were observed later, i.e. during the winter-spring period. In the warmer months March and April, the destructive potential of avalanches was noticeably smaller. In the present time, the warming and decrease of winter snowiness resulted in significant diminution of the avalanche hazard in the region. At the same time, on the background of general warming the certain increase in inter-seasonal variability of air temperature was noted. These changes may be compared to the warming of 1910–1945 when during its warmest phase the Europe suffered with one of the harshest winters in 1941/42. The swing of the «temperature pendulum» indicates that a harsh winter with heavy snowfalls and avalanches with catastrophic consequences may occur on the background of winters with mild and moderate avalanche danger. This is one of probable scenarios in the development of avalanche activity in the Greater Caucasus in the context of the current climate change.